MULTIPHASIC SCREENING: CLINICAL SYMPTOMS AND MENTAL HEALTH PATIENT TUBERCULOSIS IN JAMBI CITY, INDONESIA: Multiphasic Screening: Gejala Klinis dan Kesehatan Mental Pasien Tuberkulosis di Kota Jambi, Indonesia - M. Dody Izhar; Rizalia Wardiah; Usi Lanita; Herwansyah (Universitas Airlangga, 2023)
Background: Multiphasic screening with GeneXpert MTB/RIF and PHQ-9 is a solution for achieving successful conversion of intensive phase sputum examination. Purpose: To determine the effectiveness and feasibility of multiphasic screening for clinical symptoms and mental health in patients using the Tuberculosis Directly Observed Therapy (TB-DOTS) strategy. Methods: This study used a survey approach with a one-sample multiple testing screening method on the case finding and mental health of patients with TB. This screening was carried out in two stages: Stage I, suspected TB screening, and Stage II, mental health screening of TB patients undergoing intensive treatment (two months). Samples were taken from 160 TB suspects who came to health centers in Jambi City from August 1 to October 1, 2022, using proportionate stratified random sampling. Data were analyzed using statistical software to determine the accuracy and feasibility of screening. Results: Sputum conversion (Smear [-]) was 97.78% and the prevalence of mental health problems in patients was 22.22%. Stage I screening (suspected TB [GeneXpert MTB/RIF]): cough >2 weeks sensitivity, 94.84%; PPV, 97.35%; and accuracy, 92.50%. Stage II screening (patient mental health [PHQ-9]) with a validity of 9 items in the range of 0.17-0.66; ICC (interclass correlation coefficient [ICC], 0.60-0.83; Cronbach's a coefficient, 0.88). Multiphasic yield screening is recommended to achieve a better treatment success rate. Conclusion: Early detection of cases and mental health problems of TB patients in the early phase of treatment is a solution for developing a TB-DOTS strategy at first-level health facilities.